Role Of Government In Improving Health Anak Dalam Tribe In Sarolangun District - Usi Lanita; M. Ridwan; Yufi Afrilia Nadillah (International Journal of Health Engineering and Technology, 2024)
The Suku Anak Dalam eradication program in Sarolangun Regency continues to be carried out in an effort to eradicate poverty. Various parties have collaborated but the results have not shown sufficient success in improving welfare and health. The research aims to determine the government's role in improving health programs for the Anak Dalam Tribe in Sarolangun Regency. Data collection techniques were carried out through in-depth interviews and document reviews. This research is qualitative research with a total of 15 research informants consisting of the health office, health center, and social service. The government has made efforts to improve the welfare of the Anak Dalam Tribe community, in the health sector it has carried out education, and mass treatment. The Child Tribe Financing Program is still an obstacle in its implementation. Support from cross-sectors has yet to show good and integrated results in supporting the welfare of the tribal children. The need for sustainable program collaboration in improving the welfare of the Suku Anak Dalam. Collaboration between the government, the business world, and non-governmental organizations has the potential to accelerate the increase in the welfare of the Anak Dalam tribe.